Media Massa Yang Diminati Dan Sering Diakses Remaja Berpengaruh Terhadap Tingkat Pengetahuan Kesehatan Reproduksi Pada Remaja Sma Di Kota Denpasar Tahun 2012 - Prawira, I Made Yuda (Community Health)
Youth is the one of risk group in reproductive health. From all cases, the majority of HIVAIDS was occurred between 15-25 years old. To gain information of reproductive health, youth is prefer to choose mass media as a prior information source. This study aims to examine the influence between mass media of interest with the knowledge level of reproductive health among senior high school youth in Denpasar 2012. This study was analytical study with quantitative method and cross sectional design. Samples of 120 eleventh grade students both male and female were selected using stratified cluster sampling. Data were collected via questionnaire and analyzed statistically using chi square test. The result shows that the student’s knowledge was moderate (64.2%). Mass media of interest and frequently accessed by youth to gain reproductive health information were website (40.8%), television (24.2%), and magazine (6.7%). Among those media, the highest knowledge was gained from magazine (50%), but unfortunately youth has less interest to gain information from magazine. Mass media which is interested and frequently accessed by youth was significantly related with knowledge level of reproductive health among senior high school youth (p = 0,048). The Recommendation is The Department of Health, The National Health AIDS Commision and NGO’s which is concern to reproductive health commence to develop a recent, appropriate, and high grade reproductive health information on a website.